2017
DOI: 10.5219/755
|View full text |Cite
|
Sign up to set email alerts
|

Does apricot seeds consumption cause changes in human urine?

Abstract: Natural substances, such as amygdalin, used in alternative medicine gained high popularity. Common people as well as patients with different diseases have almost unlimited access to various natural supplements. To protect human health, it is very important to study effect of these substances. Amygdalin is a cyanogenic glucoside derived from seeds of rosaceous plants, for example seeds of bitter almonds (Prunus dulcis), or apricot, cherry, apple, peach, plum, etc. It is a natural product that owns antitumor act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…In another study, we observed decrease in calcium in human urine after 84 days of apricot seeds consumption. The same study showed decreasing tendency in urine urea (Tušimová, Kováčik et al, ; Tušimová, Zbyňovská et al, ), similarly to present work. Urea level decrease may be caused by low‐protein intake but also by liver failure or severe hepatic insufficiency (Jenkins, ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In another study, we observed decrease in calcium in human urine after 84 days of apricot seeds consumption. The same study showed decreasing tendency in urine urea (Tušimová, Kováčik et al, ; Tušimová, Zbyňovská et al, ), similarly to present work. Urea level decrease may be caused by low‐protein intake but also by liver failure or severe hepatic insufficiency (Jenkins, ).…”
Section: Discussionsupporting
confidence: 90%
“…Results of our previous apricot seeds/amygdalin studies described variety of effects, for example, small weight loss in humans after daily consumption of bitter apricot seeds (Kopčeková et al, ), significant decreasing effect on total cholesterol and LDL cholesterol levels in humans after 12 weeks of consumption (Kopčeková et al, ), effect on mineral management of the human body (Tušimová, Kováčik et al, ; Tušimová, Zbyňovská et al, ), potential impact on steroidogenesis in porcine granulose cells in vitro (Halenár, Medveďová, Maruniaková, & Kolesárová, ), but no effect on endocrine regulators in vivo (Halenár et al, ) and a slight increase in renal parenchyma dystrophy of rabbits fed apricot seeds (Kolesárová et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After consumption of apricot or bitter almond seeds, hydrogen cyanide can be produced in high enough level to pose a possible chronic toxicity problem (Miller et al, 1981;Tušimová et al, 2017). After consumption of apricot or bitter almond seeds, hydrogen cyanide can be produced in high enough level to pose a possible chronic toxicity problem (Miller et al, 1981;Tušimová et al, 2017).…”
mentioning
confidence: 99%
“…Amygdalin can be applied perorally by raw bitter apricot seeds or tablet ingestion, or by intravenous injection. After consumption of apricot or bitter almond seeds, hydrogen cyanide can be produced in high enough level to pose a possible chronic toxicity problem (Miller et al, 1981;Tušimová et al, 2017). Moertel et al (1981) observed that different ways of amygdalin administration play an important role in organism.…”
mentioning
confidence: 99%